Comparison of the Suitability Between NRS2002 and MUST as the First-Step Screening Tool for GLIM Criteria in Hospitalized Patients With GIST - Zhou, Xin; Liu, Junjin; Zhang, Qijuan; Rao, Siqi; Wu, Xingye; Zhang, Jun; Li, Juan (Frontiers in Nutrition, 2022)
Objective: The Global Leader Initiative on Malnutrition (GLIM) criteria has been recommended for malnutrition diagnosis recently, for which the first-step is malnutrition risk screening with any validated tool. This study aims to investigate the incidence of malnutrition risk in gastrointestinal stromal tumor (GIST) inpatients, and compare the suitability of Nutritional Risk Screening 2002 (NRS2002) and Malnutrition Universal Screening Tool (MUST) as the first-step screening tool for GLIM criteria. Methods: We retrospectively analyzed the clinical data of GIST inpatients in our hospital from January 2015 to December 2019. NRS2002 and MUST were used to screen malnutrition risk at the time of admission. The diagnostic consistency of these two tools with GLIM criteria for malnutrition was analyzed, and the predictive performance of both tools for the length of hospital stay and the occurrence of complications was also evaluated in surgical and non-surgical inpatients. Results: A total of 269 GIST inpatients were included in this study, of which 45.7% and 40.9% were at malnutrition risk determined by NRS2002 and MUST, respectively. In non-surgical inpatients, NRS2002 and MUST had similar diagnostic consistency with GLIM criteria in sensitivity (93.0% vs. 97.7%), specificity (81.1% vs. 81.1%) and Kappa value (K = 0.75 vs. 0.80), and high nutritional risk classified by NRS2002 and malnutrition identified by GLIM criteria were found to be associated with the length of hospital stay. In surgical inpatients, MUST had better diagnostic consistency with GLIM criteria in sensitivity (86.1% vs. 53.5%), and Kappa value (K = 0.61 vs. 0.30) than NRS2002, but no factors were found associated with the length of post-operative hospital stay or the occurrence of complications. Conclusion: The malnutrition risk is common in GIST inpatients. NRS2002 is more suitable than MUST for the first-step risk screening of GLIM scheme in non-surgical inpatients, considering its better performance in screening malnutrition risk and predicting clinical outcomes. MUST was found to have good diagnostic consistency with GLIM criteria for malnutrition in both non-surgical and surgical GIST inpatients, and further studies need to be conducted to investigate its predictive performance on clinical outcomes.